1980
DOI: 10.1111/j.1532-5415.1980.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Basis of Impaired T Lymphocyte Functions in the Elderly

Abstract: Immunologic changes associated with aging were studied by various immunologic tests in 24 aged persons (age range, 76-83) and 25 young persons (age range, 20-40). The responses to phytohemagglutinin (PHA) and concanavalin A (Con A) were depressed in the aged subjects compared to the young ones (p less than 0.05), whereas the responses to pokeweed mitogen (PWM) were similar. The activity of adhereent and non-adherent cells was assessed in various combinations. The adherent cells of aged persons were indistingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Although the nature of the autologous MLR is unknown, it has been proposed to represent the mechanism by which T cells regulate B-cell function [12]. Aged individuals who were defective with regard to autologous MLR were also defective in the Con A-inducible suppressor T-cell generation [1]. It would thus be interesting to know whether the autologous MLR and Con A-inducible suppressor function are mediated by the same or different cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the nature of the autologous MLR is unknown, it has been proposed to represent the mechanism by which T cells regulate B-cell function [12]. Aged individuals who were defective with regard to autologous MLR were also defective in the Con A-inducible suppressor T-cell generation [1]. It would thus be interesting to know whether the autologous MLR and Con A-inducible suppressor function are mediated by the same or different cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…), and PWM (Difeo Lab. ), fhe doses of PHA, Con A and PWM were determined from preliminary experiments [1].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In human studies the T cell mitogen CON A has been used to activate and delineate suppressor cell activity in vitro. Recent publications have demonstrated that CON A stimulation could mediate either enhancement or suppression, depending upon mitogen concentration 24 and time of incubation, 25 suggesting that suppression or enhancement could be opposing functions of the same cell type and may reflect different states of cellular activation.…”
mentioning
confidence: 99%